The Level of Parents' Motivation in Helping Elementary School Children during Online Learning at Home; Case Studies in Indonesia and the Philippines - Siti Dewi Maharani; Evy Ratna Kartika Waty; Sri Sumarni; Makmun Raharjo (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThe Covid-19 pandemic has affected various aspects of life, including education. For this reason, it is necessary for parents and students to work together to optimize the online learning process at home. This study aims to determine the self-efficacy of parents when helping elementary school children in doing online learning at home. This research is qualitative research approach with a descriptive quantitative analysis. The data collection method used a self-assessment questionnaire. The sample of this study was 150 parents of elementary school students, with various backgrounds and different school origins. Data were analyzed using percentage calculations. The scores were categorized by the scale and then described. The results of this study show that on average the parents of elementary school students, both in Indonesia and in the Philippines, have good motivation to help children learn from home. This can be seen from the data that the average motivation level of parents is in the good category (80.62%)Keywords: motivation, online learning, parents, self-efficacy.Â AbstrakPandemi Covid-19 telah mempengaruhi berbagai aspek kehidupan, termasuk pendidikan. Untuk itu diperlukan kerjasama orang tua dan siswa untuk membantu mengoptimalkan proses pembelajaran online di rumah. Penelitian ini bertujuan untuk mengetahui efikasi diri orang tua dalam membantu anak sekolah dasar dalam melakukan pembelajaran online di rumah. Penelitian ini merupakan penelitian kualitatif dengan pendekatan analisis deskriptif kuantitatif. Metode pengumpulan data menggunakan angket self-assessment. Sampel penelitian ini adalah 75 orang tua siswa sekolah dasar, dengan berbagai latar belakang dan asal sekolah yang berbeda. Data dianalisis dengan menggunakan perhitungan persentase. Skor dikategorikan berdasarkan skala kemudian dideskripsikan. Hasil penelitian ini menunjukkan bahwa rata-rata orang tua siswa SD baik di Indonesia maupun di Filipina memiliki motivasi yang baik untuk membantu anak belajar dari rumah. Hal ini terlihat dari data bahwa rata-rata tingkat motivasi orang tua sebesar berada dalam kategori baik (80,62%).Kata kunci: motivasi, pembelajaran online, orang tua, self-efikasi.